Social Networks and Hedge Fund Activism - He, Yazhou Ellen; Li, Tao (Review of Finance, 2022)
Abstract We study the role of social networks in hedge fund activism. Actively managed funds whose managers are socially connected to activists are more likely than unconnected managers to invest in target stocks; their investment decisions are profitable. Importantly, such effects are greater for funds facing more severe information asymmetry. Connected funds are 14.2 percentage points more likely to support activists in proxy contests and contribute to reducing proxy contest costs. Our evidence shows that social ties benefit both connected investors and activists, and suggests that social networks reduce information asymmetry around activist campaigns by facilitating information exchange and increasing trust.